The collected papers of Wei-Liang Chow - Chow, Wei-Liang 1911-1995 (World Scientific Pub. Co., 2002)
This invaluable book contains the collected papers of Prof Wei-Liang Chow, an original and versatile mathematician of the 20th Century. Prof Chow's name has become a household word in mathematics because of the Chow ring, Chow coordinates, and Chow's theorem on analytic sets in projective spaces. The Chow ring has many advantages and is widely used in intersection theory of algebraic geometry. Chow coordinates have been a very versatile tool in many aspects of algebraic geometry. Chow's theorem - that a compact analytic variety in a projective space is algebraic - is justly famous; it shows the close analogy between algebraic geometry and algebraic number theory
Keywords: Geometry, Algebraic; Algebra